Pengaruh Strategi Promosi Digital, Kemudahan Akses, Literasi Digital, Dan Kepercayaan Konsumen Terhadap Minat Penggunaan Aplikasi Pegadaian Digital Service ( Studi Pada Kantor Pegadaian Di Kota Malang ) - Anindita Cahya Mahadi; Abdul Kodir Djaelani; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the influence of digital promotion strategies, ease of access, digital literacy, and consumer trust on the interest in using the Pegadaian Digital Service (PDS) / Tring! application. The background of this research is the digital transformation in the financial sector, which has encouraged PT. Pegadaian to innovate through digital platforms. However, not all customers have fully shifted to digital services. This quantitative study used a sample of 80 respondents who were customers of PT. Pegadaian Branch Blimbing Malang and had used the PDS/Tring! application. Data were collected through a questionnaire and analyzed using multiple linear regression with the help of SPSS 25. The results showed that the variables of digital promotion, ease of access, digital literacy, and consumer trust simultaneously have a significant effect on usage interest. Partially, only the digital promotion variable has a positive and significant effect on usage interest. Meanwhile, the variables of ease of access, digital literacy, and consumer trust partially have no significant effect on usage interest. The coefficient of determination (Adjusted R²) of 0.074 indicates that 7.4% of the variation in usage interest can be explained by these four variables, while the remaining 92.6% is explained by other factors outside the model. The findings of this study imply that PT. Pegadaian needs to continue focusing on effective digital promotion strategies and providing assistance to customers, especially those less familiar with digital technology, to increase their interest in using the application. Keywords: Digital Promotion, Ease of Access, Digital Literacy, Consumer Trust, Application Usage Interest